Catalytic performance and debromination of Fe–Ni bimetallic MCM-41 catalyst for the two-stage pyrolysis of waste computer casing plastic. (June 2020) - Chen, Tao; Yu, Jie; Ma, Chuan; Bikane, Kagiso; Sun, Lushi
Abstract: A computer casing plastic waste containing brominated flame retardants (BFRs) was pyrolyzed in a two-stage vertical quartz tube reactor using iron and nickel metals modified MCM-41 catalysts. Various catalysts with different ratios of Fe and Ni were prepared and utilized to study their catalytic performance. At the presence of 20%Ni/MCM-41 catalyst, the pyrolytic yield of oil and gas reached maximum values of 49.9 wt% and 13.8 wt% respectively. The co-existence of Fe and Ni showed synergistic effect on oil composition by promoting the formation of valuable single ring hydrocarbons. With regard to the 15%Fe–5%Ni/MCM-41, 10%Fe–10%Ni/MCM-41 and 5%Fe–15%Ni/MCM-41 catalysts, the production of single ring hydrocarbons were 64.58%, 65.93% and 64.74% respectively. The bimetallic catalysts also exhibited remarkable effect on eliminating bromine from pyrolytic oil. At the presence of Fe–Ni/MCM-41, the bromine in pyrolytic oil was reduced to below 4 wt% compared with 10 wt% without catalyst. Higher amounts of Fe in the catalyst is beneficial for the debromination efficiency. The debromination process by the Fe–Ni/MCM-41 may be realized by these different mechanisms: catalytic cracking of organobromines, reaction of loaded metal oxides with HBr/SbBr3, and deposition of organobromines on the surface of catalyst. Highlights: WEEE plastics containing brominated flame retardants were pyrolyzed over catalysts. More than 64% of monocyclic compounds was obtained with bimetallic MCM-41 catalysts. The Fe–Ni bimetallic MCM-41 catalysts exhibited excellent debromination efficiency. The Br content in pyrolytic oil was less than 4 wt% with bimetallic MCM-41 catalyst. The probable debromination mechanism of the catalysts was proposed.